Navigating Water Policy: Vietnam's Strategic Shift in the Mekong River Basin (2017-2021) - Linh To Le Tran; Tam Anh Huynh Nguyen (Resolusi: Jurnal Sosial Politik, 2023)
The historic drought and salinity stress experienced in Vietnam in 2020 starkly demonstrated the criticality of wise water diplomacy for the survival of lower Mekong countries, where the urgent need for water and maintaining natural flow are paramount. Consequently, the period from 2017 to 2021 witnessed a notable shift in Vietnam's water diplomacy, focusing on ensuring water security in the region and responding to the actions of upstream countries. This study examines Vietnam's water diplomacy and its pivotal role in safeguarding water security in the Mekong region during the specified timeframe. Employing a qualitative research approach, the study draws upon expert analyses and scholarly articles to shed light on the significance of water security in Vietnam's foreign policy, the profound impact of climate change and water policies on the nation, and Vietnam's proactive involvement in regional and international cooperation mechanisms. The study emphasizes Vietnam's remarkable adaptability and responsiveness to environmental and global changes, further showcasing the country's remarkable flexibility in its foreign policy pursuits.